Kajian Kebutuhan Ruang dan Fasilitas Industri Animasi - Revian Zorna Fauzan; Farida Murti (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The animation industry is one of the creative economy subsectors that has experienced significant growth due to advances in digital technology and the increasing demand for visual content in various fields. Animation is no longer used solely as entertainment media but has also been applied in education, advertising, visual communication, and the digital gaming industry. This development has increased the need for facilities capable of supporting animation industry activities in an integrated manner. However, existing facilities tend to focus only on specific functions, such as education or production, and have not fully accommodated the overall activities within the animation industry. This study aims to examine the spatial and facility requirements needed to support animation industry activities. The research employs a literature review method by collecting and analyzing scientific journals, previous studies, and references related to the animation industry. The findings indicate that the animation industry is characterized by collaborative and technology-based work systems, requiring facilities that can support learning activities, production processes, collaboration, business development, and work promotion within an integrated environment. Keywords: animation industry, creative economy, animation facilities, spatial requirements, animation pipeline. Abstrak Industri animasi merupakan salah satu subsektor ekonomi kreatif yang mengalami perkembangan pesat seiring kemajuan teknologi digital dan meningkatnya kebutuhan konten visual di berbagai bidang. Animasi tidak hanya digunakan sebagai media hiburan, tetapi juga dimanfaatkan dalam bidang pendidikan, periklanan, komunikasi visual, dan industri permainan digital. Perkembangan tersebut menyebabkan meningkatnya kebutuhan terhadap fasilitas yang mampu mendukung aktivitas industri animasi secara terpadu. Namun, fasilitas yang tersedia saat ini masih cenderung berfokus pada fungsi tertentu, seperti pendidikan atau produksi, sehingga belum mampu mengakomodasi keseluruhan aktivitas dalam industri animasi. Penelitian ini bertujuan untuk mengkaji kebutuhan ruang dan fasilitas yang diperlukan dalam mendukung aktivitas industri animasi. Metode yang digunakan adalah studi literatur dengan mengumpulkan dan menganalisis berbagai jurnal ilmiah, penelitian terdahulu, dan referensi yang berkaitan dengan industri animasi. Hasil kajian menunjukkan bahwa industri animasi memiliki karakteristik kerja yang kolaboratif dan berbasis teknologi digital sehingga membutuhkan fasilitas yang mampu mendukung aktivitas pembelajaran, produksi, kolaborasi, pengembangan usaha, serta promosi karya dalam satu lingkungan yang terintegrasi. Kata Kunci: industri animasi, ekonomi kreatif, fasilitas animasi, kebutuhan ruang, animation pipeline.